2014
DOI: 10.1111/bju.12283
|View full text |Cite
|
Sign up to set email alerts
|

Live surgical education: a perspective from the surgeons who perform it

Abstract: Objective• To evaluate the experience and views regarding live surgical broadcasts (LSB) among European urologists attending the European Association of Urology Robotic Urology Society (ERUS) congress in September 2012. Materials and Methods• An anonymous survey was distributed via email inviting the participants of the ERUS congress with experience of LSB to share their opinions about LSB.• The outcomes measured included; personal experience of LSB, levels of anxiety faced and the perceived surgical quality.•… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…Thirteen guidelines, position statements and articles relating to guidelines placed by Surgical Societies were identified ( Table ; Table S3 , supporting information). The first guidelines were developed following the death of a patient in Japan during a live transmission in 2007.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen guidelines, position statements and articles relating to guidelines placed by Surgical Societies were identified ( Table ; Table S3 , supporting information). The first guidelines were developed following the death of a patient in Japan during a live transmission in 2007.…”
Section: Resultsmentioning
confidence: 99%
“…Khan et al demonstrated higher anxiety levels in surgeons operating in a foreign environment. Difficult communication in the operative theatre, equipment issues, and travel-fatigue appeared to have impact on the surgical performance [ 4 ]. Duty et al performed a survey investigating 90 American Association of Genitourinary Surgeons members.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of 106 European urologists who had performed live broadcasts 7% reported “significant anxiety” during the broadcast, and 16% thought that their performance had been “slightly worse,”7 although research indicates that complication rates were consistent 891011. Still, at least two patients have died in association with live broadcasts,1213 and most Japanese and US surgical societies have banned the practice 12.…”
Section: Best Interestsmentioning
confidence: 99%